1995
DOI: 10.7164/antibiotics.48.408
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features Resulting in Convulsive Activity of Carbapenem Compounds: Effect of C-2 Side Chain.

Abstract: The neurotoxicity of meropenemwas muchlower than that of both imipenemand panipenem after intraventricular administration to mice. To clarify the majorstructural features responsible for the induction of convulsions by carbapenemantibiotics, the structure-activity relationship on convulsant activity was investigated in iV-acetyl-2-pyrroline and cyclopentene derivatives which correspond to the 5-membered ring containing the C-2 side chain of carbapenem antibiotics. Among these derivatives, compoundswith strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 16 publications
(4 reference statements)
0
36
0
Order By: Relevance
“…Among these, an active metabolite accumulating with time could contribute to the observed EEG effect. Several authors have suggested that the convulsant activity of imipenem was related to the accumulation of an open lactam metabolite (18,37), but other results suggest that the parent compound itself would be responsible for the neurotoxicity (29,36). However, this metabolite is not detected in serum and cannot be included in a PK-PD model.…”
Section: Discussionmentioning
confidence: 75%
“…Among these, an active metabolite accumulating with time could contribute to the observed EEG effect. Several authors have suggested that the convulsant activity of imipenem was related to the accumulation of an open lactam metabolite (18,37), but other results suggest that the parent compound itself would be responsible for the neurotoxicity (29,36). However, this metabolite is not detected in serum and cannot be included in a PK-PD model.…”
Section: Discussionmentioning
confidence: 75%
“…The convulsant stability of carbapenems was determined as reported previously (17). Seven-week-old male ICR mice were intracerebroventricularly injected with each dose (50 to 400 g/mouse) of drugs dissolved in 5 l phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore the introduction of a double bond-conjugated to the thiazole ring-into the piperidine/pyrrolidine ring (23 and 27), which influences both the position of the cationic center, and the basicity, due to inductive effects, showed no significant effects on the anti-VREFm activity. Finally the effect of introduction of N-substituents (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) on the anti-VREFm activity is slight and smaller than that on the anti-MRSA activity.…”
Section: Carbapenems (Compounds 22-51) (Type B)mentioning
confidence: 99%
“…The product was purified by chromatography on MCI gel (CHP-20P) to give 31: IR (KBr) cm -1 3401, 1764, 1710, 1596 -methyl-7-oxo-1-azabicyclo[3.2.0]hept-2-ene-2-carboxylic Acid (32) To a solution of 23 (85mg, 0.21mmol) (33) To a solution of C30 (830mg, 1.5mmol) in EtOAc (16ml) was added iodoacetamide (550mg, 3.0mmol) at room temperature. After stirring for 30 minutes, the precipitate was separated by decantation and dried in vacuo.…”
Section: Allyl (3s)-3-[(methylsulfonyl)oxy]pyrrolidine-1-carboxylate mentioning
confidence: 99%